Wild argentinian amaryllidaceae, a new renewable source of the acetylcholinesterase inhibitor galanthamine and other alkaloids - Ortiz, Javier E. (2012)
Fil: Roitman, Gustavo Germán. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.